Mesh‐independent damage model for trabecular bone fracture simulation and experimental validation. (4th May 2021) - Do, Xuan Nam; Hambli, Ridha; Ganghoffer, Jean‐François
Abstract: We propose in this study a two‐dimensional constitutive model for trabecular bone combining continuum damage with embedded strong discontinuity. The model is capable of describing the three failure phases of trabecular bone tissue which is considered herein as a quasi‐brittle material with strains and rotations assumed to be small and without viscous, thermal or other non‐mechanical effects. The finite element implementation of the present model uses constant strain triangle (CST) elements. The displacement jump vector is implicitly solved through a return mapping algorithm at the local (finite element) level, while the global equilibrium equations are dealt with by Newton–Raphson method. The performance, accuracy and applicability of the proposed model for trabecular bone fracture are evaluated and validated against experimental measurements. These comparisons include both global and local aspects through numerical simulations of three‐point bending tests performed on 10 single bovine trabeculae in the quasi‐static regime. Abstract : A 2D constitutive model of trabecular bone fracture combining continuum damage with embedded strong discontinuity is developed. The model describes the quasi‐static three failure phases of trabecular bone tissue, and it accurately predicts the development of multiple crack patterns accompanied by a softening phase up to full failure. The enhanced triangular solid model improves the prediction of the ultimate strain and stress state of trabecular bone. The model accurately predicts the local and global bending response of single bovine trabeculae.